ANALISIS WACANA KRITIS TEUN A. VAN DIJK PADA LIRIK LAGU “TAKSU BALI” KARYA HARMONIA FEAT GUS TEJA - Ayu Putu Purnami, Ida; I Nyoman Sudiana; I Nengah Suandi; I Putu Mas Dewantara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bali is rich in natural beauty and culture, one of which is Balinese music. Balinese music with local themes is often overlooked by the public, even though it has deep meaning and specific objectives from the creator. Researchers are interested in conducting a critical discourse analysis of the lyrics of the Balinese song “Taksu Bali” by Harmonia feat Gus Teja using Teun A. Van Dijk's theory. The research method used is a qualitative descriptive method, involving reading, analyzing, and classifying the lyrics of the song “Taksu Bali” by Harmonia feat. Gus Teja using Teun A. Van Dijk's approach. The results obtained from this study are that the macro-level structural elements of the song's topic are the cultural identity crisis of Bali in the era of modernization. The superstructure contains schematic elements such as introduction, verse, pre-chorus, chorus, refrain, bridge, modulation, ending, and coda. The macro-level structure includes setting, performance, implied meaning, word choice, and metaphor usage. The results of critical discourse analysis help reveal implied messages that may not be noticed by listeners, thereby increasing critical awareness of popular cultural content. This research can serve as an important reference for researchers and cultural practitioners in exploring the hidden social and political meanings in traditional and modern musical works.